Excavations at Baturyn in 2020 and stove tiles’ reconstructions, 17th-18th c. - Mezentsev, V.I.; Sytyi, Yu.M.; Kovalenko, Yu.O. (Сіверщина в історії України, 2021)
This article overviews the findings of the 2020 excavations of remnants of the underground brick tunnel in Hetman I. Mazepa’s manor, the residences of Chancellor General P. Orlyk, and a well-to-do Cossack in Baturyn’s suburbs. It focuses on the decorations of unearthed ornamental and heraldic stove tiles in Ukrainian baroque style of the late 17th and early 18th centuries. Photos and computer graphic reconstructions of selected broken and burnt ceramic tiles as well as two façades of heating stoves of the ruined P. Orlyk’s home are presented and described.